The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/jmv.1890440213
|View full text |Cite
|
Sign up to set email alerts
|

Application of commercial assays to detect IgG antibodies to hepatitis C virus in urine: A pilot study from autopsy cases

Abstract: Hepatitis C virus (HCV), the main cause of non-A, non-B hepatitis in the United States and possibly in the world, is believed to be transmitted primarily through parenteral exposure. Many screening and supplemental tests are available to detect antibodies to HCV in serum. The ability to use commercial assays to detect antibodies to HCV in urine was investigated in this study. A total of 229 serum/urine matched samples were collected sequentially from forensic autopsy cases examined at the Office of the Chief M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
7
1
1
Order By: Relevance
“…The correlation between EIA and Western Blot in urine samples was poor, suggesting that most EIA-positive results reflected a nonspecific false positive reaction. These results differ from those of Zhang et al [1994] who reported an excellent correlation of anti-HCV detection between serum and urine. However, their study was carried out using serum and urine samples obtained from forensic autopsy cases and there is a possibility that urine samples were mixed with serum.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The correlation between EIA and Western Blot in urine samples was poor, suggesting that most EIA-positive results reflected a nonspecific false positive reaction. These results differ from those of Zhang et al [1994] who reported an excellent correlation of anti-HCV detection between serum and urine. However, their study was carried out using serum and urine samples obtained from forensic autopsy cases and there is a possibility that urine samples were mixed with serum.…”
Section: Discussioncontrasting
confidence: 85%
“…A correlation between serum antibodies and salivary or urinary antibodies has been reported in some viral infections, e.g., human immunodeficiency virus (HIV) [Archibald et al, 1986;Cao et al, 1989;Major et al, 1991;Crofts et al, 1991;Desai et al, 1991], hepatitis A virus (HAV) [Stuart et al, 1992;Parry et al, 1989], rubella [Saleh, 1991] and following immunization against polio virus [Zaman et al, 1991], rota virus [Ward et al, 1992;Friedman et al, 1993], and HAV [Hurni et al, 1993;Laufer et al, 1995]. As for HCV, oral fluid [Thieme et al, 1992;Sherman et al, 1994] and urine obtained from autopsy cases [Zhang et al, 1994] were suggested as alternative specimens for serum, for serodiagnosis of infection with this agent.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between serum antibodies and salivary or urinary antibodies has been reported in some viral infections, e.g., human immunodeficiency virus (HIV) [Archibald et al, 1986;Cao et al, 1989;Major et al, 1991;Crofts et al, 1991;Desai et al, 1991], hepatitis A virus (HAV) [Stuart et al, 1992;Parry et al, 1989], rubella [Saleh, 1991] and following immunization against polio virus [Zaman et al, 1991], rota virus [Ward et al, 1992;Friedman et al, 1993], and HAV [Hurni et al, 1993;Laufer et al, 1995]. As for HCV, oral fluid [Thieme et al, 1992;Sherman et al, 1994] and urine obtained from autopsy cases [Zhang et al, 1994] were suggested as alternative specimens for serum, for serodiagnosis of infection with this agent.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of urinary antibodies as a diagnostic tool has been investigated for certain viral diseases due to the inexpensive and non-invasive nature of sample collection 6 7 . During viral or bacterial infections, antibodies to immunoglobulins are excreted through urine, which have been found to be stable for considerable periods ( Table I ) 8 9 10 11 12 . The antibodies can be detected in urine using class-specific assays or Western blot 13 .…”
Section: Introductionmentioning
confidence: 99%